Optimizing Tax Planning and Deferred Taxes in Implementing Earnings Management - Febriana, Shandy Cahya (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2023)
The purpose of this study is to examine the optimization that occurs between tax planning and the use of deferred tax expenses in profit management implementation. Tax Planning (X1) and Deferred Tax Expenses (X2) are the research independent variables, and Profit Management (Y) is the dependent variable. The information used comes from the Miscellaneous Industry sector, with seven sample companies listed on the Indonesia Stock Exchange between 2017 and 2022. As a research method, descriptive and verification analysis is used to determine the development and influence value of variables both partially and simultaneously with data. Data was gathered from financial report data management, documents, reference books, and internet media. The results of the partial research using the t test show that the variable Tax Planning Optimization (X1) has a significant effect on profit management implementation (Y), whereas the utilization of deferred tax expenses has no effect on profit management implementation (Y). However, through the F test, these two variables have a significant influence on the implementation of profit management (Y) at the same time.